STUDENTS’ ANXIETY IN SPEAKING ENGLISH DURING DISTANCE LEARNING - Titis Pahargyan (Sanata Dharma University, Yogyakarta, 2021)
The ability to speak a foreign language is prominently influenced by one of the obstacles, namely speaking anxiety. The students tend to be anxious in speaking English in class during their presentation even though it is conducted through distance learning because of the Covid-19 pandemic. Referring to this background, this study aims to examine what kinds of the students’ anxiety in speaking English are during the distance learning and how they cope with the anxiety during the distance learning. A case study was employed in this research as one of descriptive designs in qualitative research. Moreover, the data was collected through analysing students’ self-reflection documents, a close-ended questionnaire, and an interview as the research instruments. Additionally, the participants of this study were 36 Science students at grade X of SMA Kristen Petra 1 Surabaya. After conducting the research, the researcher discovered that communication apprehension, fear of negative evaluation, and test anxiety often made the students anxious in speaking English during distance learning due to Covid-19 pandemic. Hence, it is significant for teachers as the facilitator can play their roles to reduce students’ speaking anxiety in a foreign language classroom.